Signs of Climate Change in Nordic Nature (Copenhagen : Nordic Council of Ministers, 2009)
Not only is the climate changing, our natural world is already being affected by the increase in temperature, change in precipitation and wind pattern etc. already seen. In order to track these changes, as they occur across the Nordic region, we have identified a variety of climate change signs for the Nordic nature. We present for the first time a catalogue of 14 signs that shows the impact on several ecosystems including terrestrial, marine- and freshwater. The signs have been identified using a systematic and criteria based approach that is applicable to a variety of other regions as well. In the project we show that climate change is not only affecting a few individual species or habitats in the Nordic region, but that a number of changes occur concurrently and at many scales. Important signs of climate change include, pollen and growing seasons begin earlier, fish stocks shift northwards, some bird populations decrease in numbers and other adapt by a change in migration rhythm, sensitive nature types such as palsa mires are declining in distribution, and polar bears are threatened by earlier ice-break-up.